SPIRITUAL PEDAGOGY: AN ANALYSIS OF THE FOUNDATION OF VALUES IN THE PERSPECTIVE OF BEST PERFORMING TEACHERS - Syihabuddin, Syihabuddin (International Journal of Education, 2017)
The welfare of a nation is determined by the quality of its education. The quality of education is in turn determined by the quality of teachers, and the quality of teachers by the values that guide them in performing their profession. Teachers who perform their profession based on values are best performing teachers. The question is what spiritual values guide them in fulfilling their job as a teacher? This is the main question in describing the values that become the foundation, guidelines, and motivation for teachers in performing their profession; the values that are apparent in daily life behaviors as the educational principles that become the authentic character of the teachers. To meet this goal, narrative inquiry method was employed to analyze the thoughts, feelings, and ideas of best performing teachers from the story, history or activities they recount. In order to answer the main question of this research, 24 best performing teachers from various levels of education from West Java and other provinces were gathered. Data were collected through in-depth interviews with the researcher that plays the role of research instrument. Then, the data were transcribed so that each respondent has his or her own â€narrationâ€. After getting coded and numbered, the sentences were processed with monocorn version 1.3 to find the frequency of keywords that will narrow down to certain themes potential to be the research findings. The findings were then analyzed, compared, and contrasted to tendencies as conclusions strengthened with discussion from theoretical perspectives.